PESAN MORAL DALAM PUISI “LASTU MITSLA AL-NȂSI” KARYA FARUQ JUWAIDAH (Analisis Konten) - Sammad Hasibuan; Shofiyah Binti Nasir Ilyas (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2021)
This study aims to find moral messages contained in the poem “Lastu Mitsla Al-Nȃsi” by Faruq Juwaidah. This research is a qualitative descriptive study with content analysis. Content analysis in literature is an effort to understand literary works from extrinsic aspects, including; moral messages, educational values, philosophical values, religious values ​​and historical values. The approach in this research is a philosophical and religious approach. Based on the results of research on the poem